Regional financial potential and sustainable development: lessons from Poland for Ukraine - Glazova, Yana; Kostenko, Ganna (Przegląd Wschodnioeuropejski, 2026)
This study examines the development of regional financial potential in the context of European integration by comparing Poland’s Opole region and Ukraine’s Ivano-Frankivsk region over 2004-2023. Its aim is to identify differences in the structure and dynamics of financial potential and to determine how Ukrainian regions can strengthen their financial capacity by adapting Polish best practices. The research systematises the indicators that constitute regional financial potential and proposes an original interpretation of the concept and a methodological approach to its assessment. A comprehensive analysis of the budgetary sector, business environment, and household finances reveals substantial disparities between the regions despite their similar administrative structures. These differences are most apparent in local budget revenue composition, the balance between own and borrowed capital in the business sector, and household financial autonomy. This study addresses a gap in the economic literature by offering a comparative analysis of local finances and their influence on regional development.